STUDY ON PLACEMENT OF SLIDING WALLS ON BUILDING 5 FLOOR FLOOR WITH VARIATION OF FRAME WALLS - Puji ramadhan; Meilandy Purwandito; Irwansyah Irwansyah (Program Studi Teknik Sipil, Fakultas Teknik. Universitas Samudra, 2021)
When designing a multi-storey building structure, the basic principle must be considered, namely increasing the structure's resistance to shear forces. Shear walls are one of the most common types of lateral load structures used to increase the rigidity of the structure and to absorb large shear forces as the structure increases. Previous studies have shown that shear walls will provide different performance depending on the location of the shear walls. This final project will examine the structure of flats with 5 variations of frame wall shear walls. The structure consists of 5 floors with a height of 17.6 meters and is located in the Langsa area. This research was conducted using ETABS V18 software. The results of the analysis show the value of the deviation of the 5 models. Based on the analysis of the calculations that have been carried out, it was found that the value of the deviation between floors in the 5th variation has fulfilled the permit deviation requirements based on SNI 1726:2019 for the x and y directions with the largest deviation value, namely on the 4th floor of 49.429 mm for the x direction and on the floor not of 27.935 mm for the y direction. Shear wall modeling is considered the most effective in the structure of this apartment building,namely in variation 5 it resists lateral forces such as earthquake loads and additional floors can be added using variation 5